A STUDY OF DIFFERENCES BETWEEN SEQUENCE AND SERIES WITH VARIOUS REAL APPLICATIONS - Seema; Dr. Jyoti Gupta (Innovative Research Thoughts, 2023)
In this study, we examine the differences between real analysis concepts- sequence and series. This is accomplished by conducting textbook analysis commonly used in real analysis textbooks. The differences discussed through different real life examples and applications. Arithmetic and geometric progression are studied in depth with the help of examples. Here we learn interesting methods of finding the nth term and partial sum for series. The results of this textbook analysis suggests that several differences between sequence and series do exist with a particular emphasis on functions. Implications, limitations, and future research are also discussed.